Instructor's manual to accompany Storytelling in emergent literacy - Brand, Susan Trostle (Delmar/Thomson Learning, 2001)
This Instructor's manual concludes with guidelines on how to use the storytelling videos in pre-service and in-service settings. Answers to the questions at the end of each story on the videos are also included